Do plant trichomes cause more harm than good to predatory insects?1. Issue 11 (3rd April 2014) - Riddick, Eric W; Simmons, Alvin M
Abstract Plants use trichomes as a morphological defense against attacks from herbivores. The literature was reviewed to test the hypothesis that trichome‐bearing (pubescent) plants do not cause more harm than good to predators. Forty seven records on interactions between plant trichomes and predatory insects were found. Overall, the records reveal that trichomes have more harmful than beneficial effects on predators. Fortunately, most harmful effects are sublethal; they usually affect movement, development, oviposition and predation potential. In worst cases, sticky exudates from glandular trichomes entrap predators. The hooked tips on non‐glandular trichomes impale predators. Entrapped and impaled predators often die from desiccation or starvation. Plant cultivars with high (rather than low) trichome density cause the most harm, and trichomes on tomato and some beans often cause more harm than good to predatory beetles, true bugs and lacewings. Whether these harmful effects have a net negative effect on plant fitness is poorly known and ripe for study. When developing and testing cultivars with increased trichome‐based resistance to herbivory, the question as to whether these technologies are compatible with the functional role of those predators (single or combined species) capable of suppressing herbivore populations should be considered. Published 2014. This article is a U.S. Government work and is in the public domain in the USA